Dynamics of flow around a pitching hydrofoil - Alam, Md. Mahbub; Muhammad, Zaka (Journal of fluids and structures, 2020)
This paper presents a parametric study on a forced pitching hydrofoil. The non-dimensional frequency (Strouhal number, Std) and amplitude ratio (A∗) of the hydrofoil pitching are varied as 0.21 ≤Std≤ 0.33 and 0.55 ≤A∗≤ 0.8, respectively. The numerical solution of the problem is obtained using unsteady Navier–Stokes equations. Coefficients of thrust, power, and efficiency of the hydrofoil are calculated and presented on the Std – A∗ plane. The evolution of the flow structure around the pitching hydrofoil is clarified for the conditions corresponding to both drag and thrust generations. A flow model is hypothesized. A mathematical analysis of the flow model, involving Euler, Coriolis and centrifugal accelerations in a non-inertial frame, is developed to assimilate the physical insight into the thrust generation and power input. The analysis provides theoretical relationships of thrust, power, and efficiency as functions of Strouhal number and/or amplitude ratio. The data from the numerical simulation tangibly support the relationships. This subject would be handy for undergraduate and postgraduate studies.